2016
DOI: 10.1007/s00425-016-2545-z
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal closure induced by phytosphingosine-1-phosphate and sphingosine-1-phosphate depends on nitric oxide and pH of guard cells in Pisum sativum

Abstract: Phyto-S1P and S1P induced stomatal closure in epidermis of pea ( Pisum sativum ) by raising the levels of NO and pH in guard cells. Phosphosphingolipids, such as phytosphingosine-1-phosphate (phyto-S1P) and sphingosine-1-phosphate (S1P), are important signaling components during drought stress. The biosynthesis of phyto-S1P or S1P is mediated by sphingosine kinases (SPHKs). Although phyto-S1P and S1P are known to be signaling components in higher plants, their ability to induce stomatal closure has been ambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In plant, the sphingolipid metabolite S1P involves in guard cell signal transduction (Ng et al, 2001; Coursol et al, 2003; Coursol et al, 2005; Worrall et al, 2008; Puli et al, 2016). S1P in guard triggers alteration in nitric oxide (NO), cytoplasmic calcium and cytoplasmic pH (Ng et al, 2001; Puli et al, 2016). Reactive oxygen species and cytoplasmic calcium are well known trigger of callose accumulation, probably through posttranslational regulation of callose synthases (Xu et al, 2017; Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In plant, the sphingolipid metabolite S1P involves in guard cell signal transduction (Ng et al, 2001; Coursol et al, 2003; Coursol et al, 2005; Worrall et al, 2008; Puli et al, 2016). S1P in guard triggers alteration in nitric oxide (NO), cytoplasmic calcium and cytoplasmic pH (Ng et al, 2001; Puli et al, 2016). Reactive oxygen species and cytoplasmic calcium are well known trigger of callose accumulation, probably through posttranslational regulation of callose synthases (Xu et al, 2017; Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine and 3-O-Sulfogalactosylceramide were upregulated among all other metabolites in both pollen (5.2) folds and seed (1.82) folds. Sphingosine and sphingosine 1 phosphate (S1P) regulation is interrelated and increased levels of sphingosine can bring about direct intracellular responses by increasing the cytosolic calcium concentration (Ca2+) which was also reported in Pisum sativum [42]. Phytosphingosine play import role in calcium mediated stomatal closure resulting in lesser rate of photosynthesis.…”
Section: Pathway Analysismentioning
confidence: 97%
“…Although some S1P-mediated responses are attributed to the action of an intracellular second messenger, most of the effects of S1P are thought to be receptor-mediated ( Nema et al ., 2016 ; Puli et al ., 2016 ; Ng et al ., 2017 ; Serafimidis et al ., 2017 ). The S1PR1-induced Rac1 activation was Ca 2+ dependent and that the increase in intracellular Ca 2+ was triggered by the action of PI–PLC and the IP3 receptor, it was suggested that the Ca 2+ was released from the store in the ER ( Li et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%